Improving the recipe for wheat bread by introducing various dosages of herbal sage powder - I. M. Rusina (Современная наука и инновации)
The article includes the results of research on the effect of different dosages of sage powder on quality indicators of wheat flour of the highest grade, dough and baked bread. Insignificant changes in the moisture content of mixture samples, an increase in titratable acidity, and a decrease in the weight fraction of crude gluten with simultaneous strengthening were found. High indicators of finished bread appearance of all experimental samples, good condition of crumb, change of colour, taste and smell with increasing of dosage of sage powder from 0.25 to 2.5 % of flour weight were noted. Physico-chemical indicators of wheat bread quality of all experimental samples were registered within the standardised norms. According to the results of tasting analysis the best sample containing 1.5 % of sage powder from the weight of wheat flour was selected. The selected product had high microbiological parameters at the end of shelf life. It is proposed to use sage powder as a phytoactive additive to improve the quality indicators of bread and give it a functional purpose.